Dawn in madinah: a pilgrim's passage - Iqbal, Muzaffar (Islamic Book Trust Kuala Lumpur, 2007)
Dawn in A Pilgrim's Passage is a vivid account of a month-long retreat in the Prophet's Mosque in Madinah. The luminous details of this sojourn in Islam's second-most sacred mosque are superimposed upon episodes from the life of the Prophet which forms the backdrop for the slow unfolding of a narrative filled with intense reflections on contemporary Muslim life. Woven into the tapestry of this unique book are the desires, hopes, fears, and spiritual struggles of many pilgrims who were present during the month of Ramadan in the Mosque, fourteen hundred and eighteen years after it was built by Prophet Muhammad and his Companions soon after their arrival in Madinah. This juxtaposition of contemporary lives and those lived fourteen centuries ago creates a mosaic in which one can find common threads of a journey toward God.